ANALISIS KEHAMILAN RESIKO 4T PADA IBU HAMIL DI DESA PASIRGINTUNG KECAMATAN CIKULUR KABUPATEN LEBAK TAHUN 2023 - ekayanti, ekayanti; Mutmainah, Mutmainah (LPPM STIKES BINA GENERASI POLEWALI MANDAR, 2024)
One of the reasons for the high MMR is the 4Ts, such as pregnancies that occur at too young an age, too old an age, birth intervals that are too close and too many at 22.4%. Several factors that influence health behavior are knowledge, attitudes, family support, the role of health workers and the role of health cadres. An initial survey in Pasir Gintung Village, Cikulur District, Lebak Regency found that there were 33 mothers who belonged to the 4 T group. : to determine the pregnancy risk analysis of 4T in pregnant women in Pasir Gintung Village, Cikulur District, Lebak Regency in 2023. Quantitative analysis with cross sectional design. The research sample was 95 K1 pregnant women using a total sampling technique. The research instrument used a questionnaire. The data is primary data analyzed using the chi square test. The results of univariate analysis showed that 34.7% of pregnant women were at risk of four too many, 52.6% had good knowledge, 63.2% had a positive attitude, 67.4% had family support, 65.3% supported the role of health workers, and 65.3% had a positive role. health cadres support 56.8%. The results of bivariate analysis show that there is a significant relationship between knowledge (p = 0.001), attitude (p = 0.000), family support (p = 0.002), the role of health workers (p = 0.000) and the role of cadres (p = 0.000) with pregnancy risk of four too in pregnant women. The role of health workers has a high chance of developing four-plus risk pregnancies in pregnant women with an OR of 11.960. It is hoped that midwives will carry out home visits to pregnant women who are unable to undergo examinations at health facilities so that pregnant women can receive services and obtain information from midwives